2022
DOI: 10.2147/hiv.s382219
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Uptake of Voluntary Medical Male Circumcision Among Boda-Boda Riders Aged 18–49 Years in Hoima, Western Uganda

Abstract: Introduction We asseSssed factors influencing the uptake of voluntary medical male circumcision (VMMC) among boda-boda riders aged 18–49 years in Hoima, western Uganda. Despite high levels of awareness about availability and benefits of VMMC, uptake was still low. Methods We employed the convergent parallel mixed methods design among boda-boda riders in Hoima district between August and September 2020. We administered a structured questionnaire to 316 boda-boda riders t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…In the trial within which this study was nested, we found similar outcomes between the community-led and the paid distributor arms; linkage outcomes and reports of new HIV diagnosis in the intervention arm were comparable with those using a paid distributor model [18], showing communities were able to develop models that worked for them and optimised outcomes. Our process evaluation data (not presented here) suggests barriers to linkage to post-test services some of which have been reported in other studies; the belief that linkage to post-test services is unnecessary for HIV negative people [29,30,31], poor or inaccurate knowledge of PrEP [31,32,33,34] and VMMC [35,36], fear of pain during the VMMC procedure [35,36,37] and long distances to health facilities [38]. Finally, healthcare workers shared the view that linkage works better if they are incentivised for each client linking to services [39]; incentives were not provided in this study.…”
Section: Discussionmentioning
confidence: 77%
“…In the trial within which this study was nested, we found similar outcomes between the community-led and the paid distributor arms; linkage outcomes and reports of new HIV diagnosis in the intervention arm were comparable with those using a paid distributor model [18], showing communities were able to develop models that worked for them and optimised outcomes. Our process evaluation data (not presented here) suggests barriers to linkage to post-test services some of which have been reported in other studies; the belief that linkage to post-test services is unnecessary for HIV negative people [29,30,31], poor or inaccurate knowledge of PrEP [31,32,33,34] and VMMC [35,36], fear of pain during the VMMC procedure [35,36,37] and long distances to health facilities [38]. Finally, healthcare workers shared the view that linkage works better if they are incentivised for each client linking to services [39]; incentives were not provided in this study.…”
Section: Discussionmentioning
confidence: 77%
“…For instance, older age6 44 and younger age,12 45 and being employed46 or unemployed44 have been associated with increased VMMC uptake. Sociodemographic factors that have consistently predicted VMMC uptake include higher education (secondary school and above),10 12 46 belief of improved sexual performance10 12 47 and having two or more sexual partners or high self-perceived risk of HIV 12 14 45. Other factors reported include culture/ethnicity (tribes such as Shona,48 Yao49), religion (being Muslim49), higher socioeconomic status and geographical location (urban areas) 49.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Facilitators include perceived health benefits, specifically penile hygiene and reduced risk of HIV and sexually transmitted infection (STI) acquisition, 5 enhanced sexual performance and sexual pleasure among partners of circumcised men, 5 peer or partner pressure, 9 need for social or cultural conformity 9 and advice from health personnel. 9 Additional facilitators reported by other researchers include awareness or knowledge, 10 personal VMMC experiences, 11 and formal education. 12 In addition to the barriers and facilitators, several associated/predictor factors of circumcision have been reported in Malawi.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, a study conducted in 2019 to investigate the attitudes and key challenges to VMMC adoption found that panic, perceived surgical complications, cost in accessing VMMC services, and involvement of female health workers in the circumcision team, were some of the barriers to VMMC uptake among men in Malawi [66]. Tusabe, et al, [67] in a study conducted in 2020, found that fear of pain and compulsory HIV testing, long healing time, financial constraints, perceived interruption of God's plan, loss of male fertility and involvement of female health workers were barriers to VMMC. Another study also conducted in 2020 in Namibia, found that myths and misconceptions attached to VMMC, age limitations, fear of pain and stigma associated with HIV, and long distances from health facilities negatively impacted VMMC uptake [68].…”
Section: Plos Global Public Healthmentioning
confidence: 99%